Effects of transient bottom water currents and oxygen concentrations on benthic exchange rates as assessed by eddy correlation measurements. Issue 3 (12th March 2013) - Holtappels, Moritz; Glud, Ronnie N.; Donis, Daphne; Liu, Bo; Hume, Andrew; Wenzhöfer, Frank; Kuypers, Marcel M. M.
Abstract: [1] Eddy correlation (EC) measurements in the benthic boundary layer (BBL) allow estimating benthic O2 uptake from a point distant to the sediment surface. This noninvasive approach has clear advantages as it does not disturb natural hydrodynamic conditions, integrates the flux over a large foot‐print area and allows many repetitive flux measurements. A drawback is, however, that the measured flux in the bottom water is not necessarily equal to the flux across the sediment‐water interface. A fundamental assumption of the EC technique is that mean current velocities and mean O2 concentrations in the bottom water are in steady state, which is seldom the case in highly dynamic environments like coastal waters. Therefore, it is of great importance to estimate the error introduced by nonsteady state conditions. We investigated two cases of transient conditions. First, the case of transient O2 concentrations was examined using the theory of shear flow dispersion. A theoretical relationship between the change of O2 concentrations and the induced vertical O2 flux is introduced and applied to field measurements showing that changes of 5–10 μM O2 h −1 result in transient EC‐fluxes of 6–12 mmol O2 m −2 d −1, which is comparable to the O2 uptake of shelf sediments. Second, the case of transient velocities was examined with a 2D k‐ ε turbulence model demonstrating that the vertical flux can be biased by 30–100% for several hours during changing current velocities from 2 to 10 cm s −1 . Results are compared to field measurements and possible ways to analyze and correct EC‐flux estimates are discussed. Key Points: Eddy correlation approach estimates benthic O2 uptake Eddy correlation (EC) flux is simulated for transient bottom water conditions EC flux can significantly deviate from flux across the sediment‐water interface